The Effect of Job Satisfaction and Organizational Commitment on Organizational Citizenship Behavior (OCB) in Lombok Timur Company Employees - Suraya Diniyah; Siti Nurmayanti; Sirithi Premasinghe (Tinta Emas Publisher, 2024)
This study aims to determine the effect of job satisfaction and organizational commitment on Organizational Citizenship Behavior (OCB) among employees at PT Sumber Purnama Sakti, Lombok Timur Branch Office. The research adopts a causal associative design with a quantitative approach. Data were collected using the census method, encompassing all 75 employees at the Lombok Timur Branch Office. The data were analyzed through multiple linear regression analysis. The results indicate that job satisfaction positively and significantly affects employee discipline, suggesting that employees who are satisfied with their jobs are more likely to adhere to company policies and regulations. Similarly, organizational commitment positively and significantly impacts employee discipline, indicating that employees who feel committed to the organization are more likely to maintain high levels of discipline. These findings highlight the importance of enhancing job satisfaction and organizational commitment to foster better OCB, ultimately contributing to the overall success and sustainability of the organization.